Analisis Pemahaman Mahasiswa Prodi Tadris Biologi (TBG) Dalam Penyusunan Karya Ilmiah - Septiana, Nurul (Universitas Hamzanwadi, 2020)
This study aims to (1) know the Student’s Comprehension in scientific papers, (2) to know the problem of the scientific work of the students and (3) to know some factors become the node in the paper the scientific work. The method in this research is qualitative descriptive. Techniques used in data collection is by documentation, interviews, and questionnaires. The results of this study are (1) The understanding of the students in scientific writing is 75% or the category is good enough, (2) The difficulties of students in Comprehension of scientific paper thesis proposal is being developed again, added problem, preparing hypothesis, data analysis, preparation of research design, and description of instrument that will be used in the research, (3) factors that become solution in writing scientific papers, among others, the conclusion of learning resources; the quality of negative thesis guidance is: misconceptions between supervisors with researchers, other busy lecturers, too many revisions in the proposal, and the replacement of mentors; and peer environments are: a sense of friends who have not made a thesis and hard to divide the time for working while studying.